Measuring poverty dynamics and inequality in transition economies : disentangling real events from noisy data - Luttmer, Erzo F. P. 1994- (Policy research working paper, 2001)
Estimates of income inequality and the dynamics of poverty are highly sensitive to measurement error and transitory shocks in micro-level data. The apparent high levels of economic mobility in Poland and Russia are driven largely by transitory shocks and noisy data. There is a real risk of an entrenched underclass emerging in these transition economies